2005
DOI: 10.1562/2005-08-05-ra-639
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical, Photochemical, and Tumor‐selectivity Properties of Bromine Derivatives of Rhodamine‐123

Abstract: The conceptual basis for the development of mitochondrial targeting as a novel therapeutic strategy for both chemotherapy and photochemotherapy of neoplastic diseases rests on the observation that enhanced mitochondrial membrane potential is a common tumor cell phenotype. The potential of this strategy is highlighted by the fact that the toxic effects associated with a number of cationic dyes known to localize in energized cell mitochondria are much more pronounced in tumor cells than in normal cells. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Generally, cationic PSs localize in both the nucleus and mitochondria, whereas lipophilic ones tend to incorporate into membranes [42,232,[249][250][251].…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Generally, cationic PSs localize in both the nucleus and mitochondria, whereas lipophilic ones tend to incorporate into membranes [42,232,[249][250][251].…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…24 h), show desirable morphology, are large enough to facilitate counting/analysis of drug-induced mechanisms of damage via microscopic analysis, are highly susceptible to a large variety of anticancer drugs (i.e., relatively easy to perform in vitro assays of mortality), and are also easy to manipulate and maintain (Larroque-Lombard, 2010;Lacerda et al, 2005;Belostotsky et al, 2011). The susceptibility of MES-SA cells to doxorubicin is analogous to that observed for HeLa cells (compare panels A and B in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports showed that the brominated derivatives present low to nondeterminable toxicity in different cells [48,49]. In addition, brominated thiazine derivatives exhibit decreased phototoxicity in culture cell compared to the starting reagent [50].…”
Section: Antimicrobial Pactmentioning
confidence: 99%